Investigation of the Pathogenesis and Treatment Efficiency of Bevacizumab-Induced Hypertension in the Rat Model - Mehmet Ali Balci; Musa Özgür Özyiğit; Volkan İpek; İlker Mustafa Kafa; Ender Kurt (Medical Laboratory Technology Journal, 2019)
Bevacizumab is known to reduce Vascular Endothelial Growth Factor (VEGF) to undetectable levels when used in conjunction with chemotherapy. Hypertension is a frequent adverse effect of bevacizumab, although its mechanism(s) remain unclear. In this study, our aim was to examine the pathogenesis of bevacizumab-induced hypertension and to investigate the treatment efficacy of valsartan. A total of 24 Wistar Albino female rats were included in the study. Rats were divided into three groups with 8 rats in each, as follows: The control group, bevacizumab group and bevacizumab + valsartan group. Blood pressure, blood urea nitrogen and serum creatinine levels were measured, urine samples were collected for 24 hours statistical analyses were performed using IBM SPSS 20 software pack. Nephrectomy specimens in bevacizumab and bevacizumab + valsartan groups exhibited varying degrees of renal injury. Although valsartan was able to reduce the bevacizumab-induced rise in blood pressure, it could not prevent the development of nephropathy. Conclusions these findings suggest that hypertension occurring secondary to bevacizumab treatment in rats may be associated with mechanisms involving renal injury.